2013
DOI: 10.1093/infdis/jit401
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cell Exhaustion in Human Visceral Leishmaniasis

Abstract: Little is known about CD8 T cells in human visceral leishmaniasis (VL) and it is unclear if these cells have a protective, pathological and/or suppressive function. In experimental VL CD8 T cells have been shown to contribute to parasite control and play an important role in vaccine-generated immunity. To better understand the role of CD8 T cells in human VL, we examined molecules associated with anergy and cytotoxic T lymphocytes (CTL) in peripheral blood mononuclear cells (PBMC) and splenic aspirates (SA), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 35 publications
(48 reference statements)
9
115
5
1
Order By: Relevance
“…Lymphoid cells in either the whole blood or the low-density PBMC fraction in subjects with VL express high levels of programmed cell death ligand-1 (PDL1) (Figure 6C), consistent with our prior observation of high PD1 expression on CD8 + T cells from patients with [22]. Furthermore, there was a significant increase in PDL1 expression on the surface of on LDGs from patients with VL ( Figure 6D).…”
Section: Ldg-t-cell Interactionssupporting
confidence: 88%
“…Lymphoid cells in either the whole blood or the low-density PBMC fraction in subjects with VL express high levels of programmed cell death ligand-1 (PDL1) (Figure 6C), consistent with our prior observation of high PD1 expression on CD8 + T cells from patients with [22]. Furthermore, there was a significant increase in PDL1 expression on the surface of on LDGs from patients with VL ( Figure 6D).…”
Section: Ldg-t-cell Interactionssupporting
confidence: 88%
“…Leishmania infected macrophages produces large amount of TNF-α [40] and this TNF-α can contribute to IFN-γ production by T cells and NK cells [41], so TNF-α blockade could interfere with IFN-γ secretion, as supported by our data. Neutralization of TNF-α has previously been reported to inhibit IFN-γ production by CD8 + T cells [42; 43], and we have also shown that CD8 + T cells contribute to endogenous IFN-γ production in SA cell cultures [44]. This suggest that TNF-α can induce exaggerated production of IFN-γ which induces tissue damage and pathology as seen in disease severity.…”
Section: Discussionsupporting
confidence: 66%
“…Splenocytes were stained for CD107a, CD8, CD3 and CD4 cell surface markers (Fischer Scientific) and flow cytometric acquisition and analysis was done using a BD FACS Caliber instrument (BD Biosciences, San Jose, CA). The de-granulation protocol was followed as described elsewhere (Gautam et al;Smith et al, 2009). The absolute change in CD107a expression produced by antigen re-stimulation was calculated by subtracting the value produced by unstimulated cells (baseline) from the value produced by lysatestimulated cells.…”
Section: Flow Cytometry and De-granulation Assaymentioning
confidence: 99%